Lung function in coastal and highland New Guineans—comparison with Europeans. Issue 3 (May 1973) - Cotes, J. E.; Saunders, M. J.; Adam, J. E. R.; Anderson, H. R.; Hall, A. M.
Abstract : The lung volumes, ventilatory capacity, and transfer factor of young adult male and female New Guineans living at sea level, after standardization for age, height, and, in the case of transfer factor, the haemoglobin concentration, resemble those of people of Indian and West African descent. The inspiratory capacity and expiratory reserve volume are smaller than for comparable Europeans. The highland New Guineans have a larger total lung capacity and transfer factor than the coastal dwellers due mainly to a larger inspiratory capacity. Compared with representative Europeans, the highlanders have a similar total lung capacity but larger transfer factor. The exceptional lung function of the New Guinea highlanders is not closely related to altitude and is probably determined at least in part by their present mode of life entailing a high level of habitual activity. This factor needs to be taken into account when considering `normal values'.